(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the essence and process of the formation of the Internet space, describes its content, and also describes the areas of use of these resources. As the Internet has developed as a communication network, it has been constantly enriched with various resources. In addition, the proper use of these resources has expanded.